EVALUATION OF ALTERNATIVE PROTEIN SOURCES TO REPLACE FISH MEAL IN PRACTICAL DIETS FOR TILAPIA (OREOCHROMIS MOSSAMBICUS) ADVANCE FRY - S. R. LENDE; S. I. YUSUFZAI; P. J. MAHIDA (The Bioscan, 2015)
The effects of partial replacement of dietary fish meal (FM) with plant protein sources on the growth performance and feed utilization of Tilapia Oreochromis mossambicus, were investigated. Two feeding experiments were conducted in which cotton seed meal (CSM) and soybean meal (SBM) replaced FM. Triplicates were maintained for separately for each experiment. The six isonitrogenous experimental diets were prepared which included a control diet (100% fish meal) and five treatment diets viz. fish meal replaced with cotton seed meal (Experiment- I) and soybean meal (Experiment-II) at 10%, 20%, 30%, 40% and 50% of dietary protein levels respectively. The diets were formulated to provide 40% crude protein on a dry weight basis. Fish were fed experimental diets ad libitum for 60 days. The water quality parameters were found in the permissible range during entire experimental period. After the end of Experiment-I it was found that higher weight gain (788.83±44.61), SGR (1.58±0.04), PER (1.06±0.06), survival (100±00) and lowest FCR (2.36±0.12) were obtained by feeding the fish with the diet T3 containing 30% Cotton seed meal and in experiment-II higher weight gain (711.88± 47.16), SGR (1.51±0.04), PER (0.96 ± 0.03), survival (95.00 ± 2.89) and lowest FCR (2.61 ± 0.09) were obtained by feeding the fish with the diet T3 containing 40% Soybean meal. The present study suggests that, the Cotton seed meal replacing 30% of fish meal and Soybean meal replacing 40% of fish meal in the diet of O. mossambicus advance fry gave better growth.